INTEGRATING LITERACY, STEM, AND FINANCIAL LITERACY OF ASNAF YOUTH FOR SUSTAINABLE DEVELOPMENT - Hanafi, Abdul Ghafur; Nor, Nainatul Farzuha; Subri, Nor Izham; Mustafa, Wan Azani (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates the integration of literacy, STEM (Science, Technology, Engineering, and Mathematics), and financial literacy as a strategic approach to empower Asnaf youth in Perlis, Malaysia, and support sustainable development. Using a mixed-methods research design, we collected data from 119 Asnaf youth enrolled in three secondary schools through a structured questionnaire. The findings reveal varying levels of knowledge and interest in these domains, with notable challenges, including limited access to educational resources, insufficient parental support, and gaps in practical financial skills. Despite some awareness of financial concepts, various respondents exhibited patterns of dependency on borrowing and inconsistent budgeting practices. The study proposes an integrated educational model tailored to the socio-cultural and religious context of Asnaf youth, incorporating Islamic values and guided by the Majlis Agama Islam Negeri Perlis (MAIPs). Recommendations include strengthening digital literacy, promoting emergency savings habits, and implementing community-based learning programmes. By addressing educational disparities among marginalised Muslim youth, this study contributes to both academic discourse and policy development in youth empowerment, aligning with national development goals and Islamic principles of Zakat-based social upliftment.